A Study of “Tradition” in Ziauddin Sardar’s “Surviving Postmodernism” and Paul Gilroy’s “Not a Story to Pass On: Living Memory and the Slave Sublime” - Ghimire, Rishiram (Humanities and Social Sciences Journal, 2022)
This article is concerned with the study of ‘Tradition’ in Ziauddin Sardar’s essay“Surviving Postmodernism (1997)” and Paul Gilroy’s “Not a Story to Pass On: Living Memory and the Slave Sublime (1993)” which discuss on non-Western culture and black cultural production respectively. Both essays have entailed the issue of ‘tradition’ and the problem with tradition in Western society is that being traditional is to become parochial and regressive by ignoring the progress of modernity whereas in the eastern society it is a way of moving ahead protecting cultural values with proper refinement. In this regard, this article purports to excavate the ground of tradition in both societies. The nub of these two essays is that tradition is not the exact opposite of modernity and progress, it is rather a force to bridge past and present in an innovative way and a medium to trace back the history and heritage of any community. Sardar sees power in tradition to survive postmodernism and Gilroy finds tradition in black cultural production a potency to revisit African roots. In both culture, spiritual civilization is the basis of their activities, which inhere force to defuse fragmentation caused by material civilization. The researcher has studied ‘tradition’ as a tool of analyzing the two essays under scrutiny.